2022
DOI: 10.1021/acs.orglett.2c00700
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Hydrogen Atom Transfer Hydroarylation of Alkenes toward δ-Lactams Using Cobalt-Photoredox Dual Catalysis

Abstract: Intramolecular hydroarylation of alkenes through hydrogen atom transfer (HAT) represents a robust method to prepare benzo-fused heterocycles. However, the reported methods have limitations in a variety of accessible cyclic scaffolds. Here we report a dual cobalt- and photoredox-catalyzed HAT hydroarylation of alkenes that is characterized by higher efficiency in the synthesis of a δ-lactam compared to established protocols. The proposed mechanism is supported by experiments and DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 59 publications
(16 reference statements)
0
9
0
1
Order By: Relevance
“…Shenvi developed a simplified system for the hydrogenation of monosubstituted alkenes using catalytic Co­(OAc) 2 and HCl . Recently, Kojima and Matsunaga reported a dual cobalt-photoredox approach for the hydrogenation and intramolecular hydroarylation of alkenes (Scheme B) . Baran et al demonstrated electroreductive generation of Co III –H in the context of alkyne hydrogenation, alkene isomerization, and related transformations .…”
mentioning
confidence: 99%
“…Shenvi developed a simplified system for the hydrogenation of monosubstituted alkenes using catalytic Co­(OAc) 2 and HCl . Recently, Kojima and Matsunaga reported a dual cobalt-photoredox approach for the hydrogenation and intramolecular hydroarylation of alkenes (Scheme B) . Baran et al demonstrated electroreductive generation of Co III –H in the context of alkyne hydrogenation, alkene isomerization, and related transformations .…”
mentioning
confidence: 99%
“…1b). 4 In spite of practical utilities, 5 these methods suffer from limitations regarding narrow substrate scope, harsh reaction conditions with strong acid additives and transition metal residues in the products. Radical couplings provide versatile tools for bond formation in molecule synthesis, 6 and have also been explored for the hydroarylation process.…”
mentioning
confidence: 99%
“…Earth-abundant first-row transition-metal hydrides can formally add a hydrogen atom to alkenes to generate a carbon-centered radical. Pioneering work in this field has demonstrated that this can be combined with a variety of radical traps, and applications include intra- and intermolecular hydroarylation reactionseither using activated heteroarenes or via the combination with nickel catalysis . However, styrenes have proven to be a challenging class of olefin for these methods.…”
mentioning
confidence: 99%